LITERATURE REVIEW: KESIAPAN RUMAH SAKIT INDONESIA DALAM PENERAPAN GREEN HOSPITAL - Rum, Malihah Ramadhani; Nursanty, Oci Etri (Journal of Hospital Administration and Management (JHAM), 2024)
​​ In the endeavor to enhance the quality of healthcare services, Indonesia possesses a substantial number of hospitals, aiming to establish each hospital as an integrated ecosystem amidst the challenges posed by climate change, global warming, and environmental degradation. The imperative of sustainability underscores the need to preserve the quality of the environment and judiciously utilize natural resources. Systematic initiatives are underway to enable hospitals to effectively harness natural potentials and embrace nature-based, environmentally friendly resources such as clean water, energy, paper, and other materials essential for daily hospital operations. This study employs a literature review methodology, commencing with selecting a topic and determining search parameters for relevant journal articles. The chosen database for this inquiry is Google Scholar, with the search focused on publications spanning the years 2014 to 2023, utilizing the keyword 'Green Hospital.' Nine Indonesian journals were selected based on predetermined inclusion criteria, emphasizing the implementation of Green Hospital practices in Indonesia. Numerous hospitals in Indonesia have undertaken diverse measures to align with the principles of green hospitals. These measures encompass enhancements in energy efficiency, adoption of green building design, exploration of alternative energy sources, sustainable transportation practices, eco-conscious approaches to food consumption, waste management strategies, and judicious use of water resources. While acknowledging that the implementation may not have achieved 100% compliance with prescribed standards, it is noteworthy that most Indonesian hospitals have initiated and executed the adoption of green hospital practices in a phased manner.